The Public Procurement Tribunal and the effectiveness in the way to restore the rule of law. New regulation, same results? - Ruiz Ibáñez, Andrés (Revista de Derecho Público, 2024)
At paper puts forward a criticism concerned the Chilean model of claims in the public pre-contractual sphere, in terms of the effectiveness of the measures adopted by the Public Procurement Tribunal to restore the rule of law. Based on solutions provided by comparative law, it tries to identify key elements that determine its effectiveness, and the reasons why, in the author’s opinion, the regulation established in the recent Law 21.634 hinders an effective judicial protection. Finally, weighting criteria are proposed when Public Procurement Tribunal must grant any relief, which attempts to overcome the protection, in any event, of the irregular contractor.